2021
DOI: 10.36880/c13.02502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Direct Investment on Poverty Reduction in Turkey: A Time Series Analysis

Abstract: Foreign direct investment can be outlined as the net inflows of investment to take possession of permanent management. Foreign direct investments can support poverty alleviation especially for developing countries which needs capital. Global foreign direct investment sums $1.5 trillion in 2019 decreased to a calculated $859 billion in 2020 as the UNCTAD report indicates. Foreign direct investment flows are expected to remain weak with uncertainty due to Covid-19. For almost 25 years, extreme poverty, was stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…It should be noted, according to the results of our estimates, that there is no significant impact between FDI and domestic investment GCF on extreme poverty in both regimes. Our findings regarding the relationship between FDI and poverty reduction are in opposition to those obtained by Tsaurai (2023), Algan et al (2021), Topalli et al (2021), Ahmad et al (2019), Ngo (2019), Tsaurai (2018), Fowowe andShuaibu (2014), andJalilian andWeiss (2002), who showed that FDI contributes positively and significantly to poverty reduction. Also, our results are not consistent with those obtained by Bornschier and Chase-Dunn (1985), who found that FDI exacerbates poverty.…”
Section: Dynamic Panel Threshold Estimationcontrasting
confidence: 99%
“…It should be noted, according to the results of our estimates, that there is no significant impact between FDI and domestic investment GCF on extreme poverty in both regimes. Our findings regarding the relationship between FDI and poverty reduction are in opposition to those obtained by Tsaurai (2023), Algan et al (2021), Topalli et al (2021), Ahmad et al (2019), Ngo (2019), Tsaurai (2018), Fowowe andShuaibu (2014), andJalilian andWeiss (2002), who showed that FDI contributes positively and significantly to poverty reduction. Also, our results are not consistent with those obtained by Bornschier and Chase-Dunn (1985), who found that FDI exacerbates poverty.…”
Section: Dynamic Panel Threshold Estimationcontrasting
confidence: 99%
“…The study noted that FDI reduced poverty, especially unemployment, but not in areas linked to the production sector capacity. Algan et al (2021) investigated the linkage between poverty and FDI in Turkey using time series data from 1996 to 2019. Household consumption expenditure was used as a proxy measure, and FDI was found to reduce poverty.…”
Section: Foreign Direct Investment-led Poverty Alleviationmentioning
confidence: 99%
“…However, Bornschier and Chase-Dunn (1985) argued that FDI reliance is not good for long-term growth and poverty reduction. Empirical research exists to support the notion that FDI triggers poverty reduction (Algan, Bal, & Bayraktar, 2021;Jalilian & Weiss, 2002;Topalli, Papavangjeli, Ivanaj, & Ferra, 2021;Ucal, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation has led to a limited number of empirical studies in the field of economics in Türkiye that use time series analyses related to poverty. This constraint has been overcome in the literature by using per capita household final consumption expenditures (HFC) as a proxy variable (Şahbaz et al, 2016;Usman, 2018;Algan et al, 2021;Sikandar et al, 2021;Sürücü et al, 2021;Ersoy & Karşıyakalı, 2022;Olaniyi & Odhiambo, 2024) for poverty. Therefore, in this study, per capita household final consumption expenditures were used for the poverty indicator, which is the dependent variable.…”
Section: Introductionmentioning
confidence: 99%